Генезис та вік циркону із амфіболіту новокриворізької світи Криворізької сруктури - Степанюк, Л.М.; Бобров, О.Б.; Паранько, І.С.; Пономаренко, О.М.; Сергєєв, С.А. (Мінералогічний журнал, 2011)
За допомогою методів оптичної та електронної мікроскопії вивчено морфологію та анатомію кристалів циркону із амфіболіту нижньої метабазитової частини Криворізької структури. Встановлено, що кристали циркону представлені кількома різними за оптичними характеристиками генераціями. З використанням іон-іонного мікрозонду Shrimp II вивчено уран-свинцеві ізотопні системи різних генерацій циркону. Встановлено декілька різновікових зон росту (генерацій) кристалів циркону: 2,97, 2,83—2,80, 2,03—2,00 і 1,78 ± 0,01 млрд рр. Припущено, що кристалізація перших трьох пов’язана зі структурно-метаморфічними перетвореннями базальтів, ці перетворення відбулись під час закладання Криворізького басейну та формування порід криворізької серії. Кристалізація циркону віком 1,78 ± 0,01 млрд рр., імовірно, пов’язана з ендогенними процесами, що обумовили формування Корсунь-Новомиргородського плутону та уранового зруденіння альбітит-уранової формації. С помощью методов оптической и электронной микроскопии изучены морфология и анатомия кристаллов циркона из амфиболита нижней метабазитовой части разреза Криворожской структуры. Установлено, что кристаллы циркона представлены несколькими генерациями с разными оптическими характеристиками. С использованием ион-ионного микрозонда Shrimp II изучены уран-свинцовые изотопные системы разных генераций циркона. Установлено несколько разновозрастных зон роста (генераций) кристаллов циркона: 2,97, 2,83—2,80, 2,03—2,00, 1,78 ± 0,01 и 1,14 млрд лет. Предполагается, что кристаллизация первых трех связана со структурно-метаморфическими преобразованиями базальтов, происходившими во время заложения Криворожского бассейна и формирования пород криворожской серии. Кристаллизация циркона возрастом 1,78 ± 0,01 млрд лет могла быть связана с эндогенными процессами, обусловившими формирование Корсунь-Новомиргородского плутона и уранового оруденения альбитит-урановой формации. Kryvyi Rig structure is confined to boundary of two different in afes megablocks of the Ukrainian Shield — Ingul’sk comprized by metamophosed volcanic-sedimentary and gra nitic formations of Paleoproterozoic age (granite-metasedimentary structural-formational complex), and Middle Dnieper which geological background is manifested by plagiogranites and plagiomigmatites of Dnipropetrovs’k complex with relicts of Aul’sk group in which Mesoarchean greenstone structures are "enclosed". Such position of the Kryvyi Rig structure in structurally-tectonic ensemble of the Ukrainian Shield was reflected in history of its geological development which displays a number of important and, probably, enough long stages of formation of the Ukrainian Shield that allows to hope on establishment in its section of "physical boundary" between Archean and Proterozoic. The decision of this problem is possible only by isochronous dating of metabasites from bottom part of metavolcanic-sedimentary section of the structure, which is traditionally considered as stratotype of lower Proterozoic of the Ukrainian Shield. Peculiar feature of this part of the section is the stable paragenesis of metadacites, metaandesites and metatholeites which, according to their petrochemical features, are similar to rocks of daciteandesite- tholeiitic formation of greenstone structures of Middle Dnieper. At the bottom section of the complex the pack of so-called Lativka quartzites occurs and results of local dating of cores of clastogene zircon selected from them were discussed in our previous publication. Morphology and anatomy of zircon crystals from am phibolite of metabasic part of bottom section of the Kryvyi Rig structure are studied by the methods of optical and electronic microscopy. It is established, that zircon crystals are represented by several generations, which differ in optical characteristics. Uranium-lead isotopic systems of different generations of zircon are studied by ion-ionic microprobe Shrimp II. Several different in age growth zones (generations) of zircon crystals are established: 2.97, 2.83—2.80, 2.03—2.00, 1.78 ± 0.01 and 1.14 Ga. It is supposed, that crystallization of former three is connected with structural-metamorphic transformations of basalt that occur in initial stage of Kryvyi Rig basin and formation of rocks of the Kryvyi Rig group. Crystallization of zircon aged at 1.78 ± 0.01 Ga could be connected with endogenic processes, which have caused formation of a Korsun’-Novomyrgorod pluton and uranium mineralization of al bitite-uranium formation. Dating of 1.14 billion years has no logic explanation as for today there are no data about manifestation, at this time, of endogenic processes in the Kryvyi Rig structure, or in adjacent sites of earth crust.